Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Disiplin Kerja Guru di SMA Nasional Makassar - Nasir, Nasir (Universitas Methodist Indonesia, 2024)
Teachers' work discipline is one of the key factors that affect the effectiveness of the learning process in schools. However, challenges such as lack of supervision, low motivation, and poor time management often hinder the achievement of optimal work discipline. This study aims to analyze the role of school principal leadership in improving teacher work discipline at Makassar National High School. The research uses a qualitative descriptive approach, with data collection techniques in the form of interviews, observations, and documentation. The subjects of the study include school principals, teachers, and school staff. The results of the study show that the leadership of school principals plays a significant role through the implementation of directed supervision strategies, continuous motivation, and consistent rule enforcement. The principal also demonstrates the ability to build effective communication and set an example of discipline. As a result, there is an increase in teacher discipline in terms of attendance, punctuality, and fulfillment of administrative and teaching duties. This study recommends strengthening leadership training programs for school principals to support the achievement of better work discipline in the school environment.